2014
DOI: 10.2298/vsp120906041a
|View full text |Cite
|
Sign up to set email alerts
|

Do women in rural areas of Serbia rarely apply preventive measures against cervical cancer?

Abstract: This study shows that women in rural areas rarely implement preventive gynecological measures againt cervical cancer in comparison with those in urban areas. Implementation of preventive measures among rural women is conditioned by lower levels of education and lower socioeconomic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…Nonetheless, rural areas have limited access to these services due to inadequate infra-structure and other related rural hindrances to healthcare facilities. Previous studies conducted abroad showed lower cancer screening rates in rural areas compared to urban areas due to socio economic disparity [ 41 , 42 , 43 ]. However, this could not be compared to the situation in Korea, as it has a NCSP.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, rural areas have limited access to these services due to inadequate infra-structure and other related rural hindrances to healthcare facilities. Previous studies conducted abroad showed lower cancer screening rates in rural areas compared to urban areas due to socio economic disparity [ 41 , 42 , 43 ]. However, this could not be compared to the situation in Korea, as it has a NCSP.…”
Section: Discussionmentioning
confidence: 99%
“…3 Kao najznačajnije faktore, brojne studije su izdvojile faktore vezane za rizično seksualno ponašanje (rani početak seksualne aktivnosti, veći broj seksualnih partnera, SPB u anamnezi, faktore vezane za muškog partnera), dugotrajnu primenu oralnih kontraceptiva, sociodemografske faktore (loši socio-ekonomski uslovi, niži nivo obrazovanja, godine), kao i faktore vezane za organizaciju preventivne zdravstvene zaštite (nesprovođenje skrining programa). [4][5][6][7] Karcinom grlića materice je preventabilan ako se dijagnostikuje u ranoj fazi obolevanja, obzirom da ima dugu premalignu fazu, da je lečenje premalignih promena izuzetno efikasno, kao i zahvaljujući dobro organizovanim skrining programima. Krajem 2012. godine, primena organizovanog skrininga putem citologije (PAPA bris) je počela u šest Domova zdravlja -dva u Beogradu (Paliluala i Stari grad) i četiri u unutrašnjosti zemlje (Novi Sad, Niš, Kraljevo i Kruševac).…”
Section: Uvodunclassified
“…Žene iz ruralnih područja Srbije su u povećanom riziku za rak grlića materice u odnosu na žene urbanih područja, obzirom da su manje obrazovane, lošijeg socio-ekonomskog statusa, starije životne dobi i ređe sprovode preventivne prakse za rak grlića materice. 4 Nedostatak znanja žena u Srbiji o reproduktivnom zdravlju, loši stavovi ginekologa i lične prepreke povezane sa negativnim iskustvom u primarnoj zdravstvenoj zaštiti, uslovljavaju nizak prioritet preventivne prakse, kako za žene, tako i za ginekologe. 5,6 To su razlozi što se traže alternativne metode skrininga.…”
Section: Uvodunclassified